Strategi Pengembangan Wisata Rembangan: Optimalisasi Wahana ATV Untuk Menarik Minat Gen Z - Fuad, Mohamad Zakaria Husni; Azzain, Abdullah Faqih; Rohim, Muhammad Abdur; Musari, Khairunnisa (CV. ITTC INDONESIA, 2025)
Rembangan Tourism is one of the tourist destinations in Jember Regency which offers various facilities such as hotels, restaurants and swimming pools. However, the number of visits from young people, especially Gen Z, is still relatively low. To overcome this problem, the management added ATV rides to attract the interest of the younger generation. From a sharia economic perspective, tourism development must pay attention to the principles of justice, benefit and sustainability. This research aims to analyze the effectiveness of ATV rides in increasing the interest of Gen Z and evaluate their management based on sharia economic principles. The method used in this research is a qualitative approach with direct observation, interviews with managers and visitors, and secondary data analysis. The research results show that ATV rides have great potential to attract Gen Z, especially if combined with digital marketing strategies based on halal tourism and sharia values. Apart from that, Rembangan tourism also needs to consider sustainability aspects in its management so that it remains in line with sharia economic principles and can provide long-term benefits for the surrounding community.